The Low Temperature Chamber Testing of the Compression Ignition Engine and System of the Armoured Personnel Carrier (APC) M113A1. - Webster,G D; Glass,R G; Hutton,G J (1981)
A study has been undertaken to validate and supplement data observed during the February 1978, Alert (NWT) low temperature starting tests for the Canadian Forces Armoured Personnel Carrier M113A1. The cold chamber testing found the M113A1 compression ignition (CI) GMC6V53 engine to have a somewhat reduced starting capability than was observed for the Arctic testing. The No-Start Temperature-T(NS) using 10 oil and type AA fuel for the tests of this study was T(NS) or = -20 deg C T(NS) or = -22 deg C for the Arctic Tests). It is believed that traces of water vapour in the fuel may have contributed to this discrepancy. The T(NS) for the Arctic grade synthetic oil DN 600 and Type AA fuel was T(NS) or = -22 deg C. The report describes in detail the systems used for instrumentation, experimentation and data analysis. This detail has been provided to assist those that wish to continue the work of this study. A number of conclusions have been drawn and recommendations made for areas of required future effort. The report is concluded with an overall general discussion that summarizes and suggests an approach to improve the cold starting capability of CF compression ignition combat vehicle powerplants. (Author) Abstract in French.